Thermodynamic assessment of the Al–Mo–V ternary system - Hu, Biao; Yao, Bin; Wang, Jiong; Zhao, Jingrui; Min, Fanfei; Du, Yong (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Thermodynamic assessment of the Al–Mo–V ternary system was performed by means of the CALPHAD (CALculation of PHAse Diagram) approach based on the thermodynamic descriptions of three constitutive binary systems (Al–Mo, Al–V and Mo–V) as well as the experimental phase equilibria data available in the literature. The solution phases, i.e. liquid, bcc (Mo, V) and fcc (Al), were described using the substitutional solution models with the Redlich-Kister equation. The binary phases in the Al–Mo and Al–V systems with the solubilities of the third element were modeled using the sublattice models. An optimal set of thermodynamic parameters for the Al–Mo–V system was obtained. Six isothermal sections at 1200, 1000, 750, 715, 675 and 630 oC and liquidus projection with isotherm were calculated. The reaction scheme for the entire Al–Mo–V system was also constructed. Comparisons between the calculated and measured phase diagrams indicated that almost all the reliable experimental information was satisfactorily accounted for by the present modeling.
Keywords: Al–Mo–V system; CALPHAD approach; Isothermal section; Liquidus projection